2015
DOI: 10.4049/jimmunol.1303089
|View full text |Cite
|
Sign up to set email alerts
|

The Unappreciated Intracellular Lifestyle of Blastomyces dermatitidis

Abstract: Blastomyces dermatitidis, a dimorphic fungus and the causative agent of blastomycosis, is widely considered an extracellular pathogen, with little evidence for a facultative intracellular lifestyle. We infected mice with spores - the infectious particle - via the pulmonary route and studied intracellular residence, transition to pathogenic yeast and replication inside lung cells. Nearly 80% of spores were inside cells at 24 hours after infection with 104 spores. The majority of spores were located inside of al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 42 publications
1
31
0
Order By: Relevance
“…Innate immune cells play a critical role in regulating the pathogenesis of this infection. Neutrophil recruitment helps to limit the initial growth of the pathogen, as depletion of neutrophils yields an increase in the lung fungal burden by 2 days post infection . Recent studies by Hernandez‐Santos et al .…”
Section: Type 17 Responses To Pulmonary Mycosesmentioning
confidence: 99%
See 1 more Smart Citation
“…Innate immune cells play a critical role in regulating the pathogenesis of this infection. Neutrophil recruitment helps to limit the initial growth of the pathogen, as depletion of neutrophils yields an increase in the lung fungal burden by 2 days post infection . Recent studies by Hernandez‐Santos et al .…”
Section: Type 17 Responses To Pulmonary Mycosesmentioning
confidence: 99%
“…Several studies have interrogated host immunity in response to fungal spores, but most animal studies of immunity to dimorphic fungal infection to date have been performed with the yeast‐like form of the fungi. This is in large part due to technical difficulties in generating pure populations of spores and biosafety concerns of handling infectious spores when performing animal infections.…”
Section: Type 17 Responses To Pulmonary Mycosesmentioning
confidence: 99%
“…Recent investigation has demonstrated that conversion to yeast is accelerated following phagocytosis of B. dermatitidis spores by alveolar macrophages. 55 In addition to intracellular spore germination, yeasts are able to survive and replicate within macrophages during the early stages of infection. 55 Thus, B. dermatitidis exhibits an intracellular lifestyle, which is similar to other dimorphic pathogens including H. capsulatum, Coccidioides spp., and Paracoccidioides brasiliensis.…”
Section: Pathogenesis Overviewmentioning
confidence: 99%
“…Peak concentrations varied widely (0.01 ng/ml to above the limit of quantification). This may reflect the increased excretion of antigen after the death of fungal cells, the transient increase in fungal load from macrophage uptake after initiation of antifungal medication, or differences in location or severity of infection (30). Two patients converted to positive within 1 month of starting treatment, and 4 patients reverted to negative within 30 days of starting antifungal medications.…”
mentioning
confidence: 99%